Improving Community Welfare Through the Management of Muara Muntai Ulu Village Funds, Muara Muntai District, Kutai Kartanegara Regency - Kuryadi, K.; Daulay, Pardamean; Rulandari, Novianita (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the effectiveness of Village Fund management in improving community welfare in Muara Muntai Ulu Village, Muara Muntai District, Kutai Kartanegara Regency. Although Village Funds have been directed to finance various priority sectors, including basic infrastructure development, education, health, and community economic empowerment, their implementation still faces several challenges. This study used a qualitative research method with a descriptive-analytical approach. The results show that, although Village Fund management in Muara Muntai Ulu Village has generally achieved positive outcomes in increasing access to basic services and promoting economic empowerment, significant obstacles remain that hinder the policy's effectiveness. These obstacles include the limited capacity of village officials in planning and reporting, suboptimal community participation, inaccurate beneficiary data, and weak coordination between village institutions. In addition, the suboptimal utilization of Village Funds for productive economic innovation and a weak monitoring system are also challenges. Therefore, institutional capacity building, data system improvements, and mainstreaming of public participation are needed so that Village Funds truly contribute to community welfare comprehensively and sustainably.